Trabajadoras latinoamericanas en España: Migraciones laborales y género - Arellano Millán, María (Cuadernos de Relaciones Laborales, 2006)
The Latin American immigration that reside in Spain, is different from other immigration groups, and that is because the high feminine representation and the link of this women to the salaried work in place. Understanding that immigration is a kind of a system and pointing out as it basic variable, the gender and the working labour, the present article identify in first place, the factors that in their origin and destination make possible the formation of an economical immigration running, pointing up, the high feminine participation related with the salaried work. In second place, we can analyze the characteristics and working situation from the housework to finally emphasize the functionality that in their working integration exert in the labour working market and the own Spanish society.
Keywords: Immigration; Labour relations; Gender; Social networks; Migrations; Work force; Latin america